Cultural Differences and the Construction of Meaning - Peña, Robert A. (Education Policy Analysis Archives, 1997)
The relationships between student achievement, student culture and practitioners' attitudes and expectations were investigated. Student achievement was defined as academic performance but also included perceptions, rationales and explanations for student behaviors and conduct. Student culture described student's Mexican American origins, customs and beliefs. Practitioners' attitudes described how middle school personnel perceived Mexican American high and underachieving students generally, and practitioners' expectations described how personnel interacted and behaved toward Mexican American students. Results indicated that Mexican American students perceived themselves and school personnel perceived these students as different from Anglo students. Mexican American cultural traditions were also perceived as inferior and disadvantageous by high achieving Mexican American students and by personnel. Underachieving Mexican American students generally valued their cultural traditions more positively than high achieving students becoming resistant to learning when these traditions were marginalized in school. Student achievement was also related to student compliance, student appearance, styles in written and verbal communication and practitioners' perceptions about the willingness of Mexican American students to practice and support Anglo norms. These findings are congruent with theories that discuss relationships between student achievement, student culture and practitioners' attitudes and expectations. Theories about school failure occurring less frequently in minority groups that are positively oriented toward their own and the dominant culture were contradicted and not supported in this research.